Sint-Amandus. Jacob van Artevelde en zijn tijd. Lieven Bauwens. - Vanden Gheyn, Jos; Storme, Jules; Beeckman, B.-G. (Gent : Het Volk)
Bibliotheek E. Anseele
Nederlands
Brochure
Keywords: Bauwens, Lieven; Van Artevelde, Jacob